Integrasi Sistem Informasi Geografis dan Sistem Informasi Manajemen Keanggotaan untuk Meningkatkan Aksesibilitas Layanan Kesehatan pada Ikatan Dokter Indonesia (IDI) Cabang Malang Raya - Rozi, Imam Fahrur; Ariyanto, Rudy; Arianto, Rakhmat; Hapsari, Ratih Indri; Ananta, Ahmadi Yuli; Rohadi, Erfan; Widito, Sasmojo; Zakaria, Arief Syukron; Budiarti, Arry; Saputra, Zainal Ulu Prima; Irawan, Ferry Buyung Bakhtiar; Sholiha, Afifah (J-Dinamika : Jurnal Pengabdian Masyarakat, 2025)
The Indonesian Medical Association (IDI) Chapter Malang Raya, which covers area of Malang City, Batu City, and Malang Regency, faces challenges in managing doctor membership data and presenting information related to customer services and public services. To overcome these obstacles, a website-based information system was developed that integrates the Membership Management Information System with the Geographic Information System (GIS). The Membership Management Information System facilitates efficient management data of physician member of IDI chapter Malang Raya, including status of membership, competence of medical doctors, speciality, and subspeciality. Whereas GIS system serves to map the location of doctor practices. Integration these two systems making it easier for people to find the nearest health services. The system was developed using the waterfall methodology, which involves the stages of requirements analysis, design, implementation, testing and maintenance. The result is a platform that can improve IDI's internal efficiency and make it easier for people to access health services. This system has the potential to be further developed with the addition of security features and functionality such as real-time monitoring and mobile application integration, thus supporting more responsive and integrated health services